Correlation Between Kidney Function and Intestinal Biological Characteristics of Adenine and Folium SennaeInduced Diarrhea Model in Mice - Li, Xiaoya; Zhu, Jiayuan; Wu, Yi; Tan, Zhoujin (Turkish Journal of Gastroenterology, 2022)
Background: This study investigated the correlation among kidney function, intestinal enzyme activities, and microbial activity of adenine and Folium sennae-induced diarrhea model in mice, which provided a basis for clinical treatment of kidney-intestinal correlation.Methods: We performed different doses of adenine combined with Folium sennae intragastric administration to establish the animal model of diarrhea. We assessed thymus and spleen indexes, serum creatinine, urea nitrogen and uric acid contents, intestinal contents and mucosal enzyme activities, and microbial activity.Results: After modeling, mice presented increased serum creatinine and decreased urea nitrogen. Uric acid showed different changes in the different model groups. The thymus index in the model mice was trending downward, whereas the spleen index was the opposite. Moreover, model mice induced a non-significant increase in xylanase activity of the intestinal contents and mucosa compared to the control performance. Sucrase content of the intestinal contents increased considerably in the model groups but decreased in the intestinal mucosa. Lactase and amylase induced different trends in the different modeling methods. As well, the microbial activity of intestinal contents increased significantly, while that of intestinal mucosa decreased.Conclusion: Adenine combined with Folium sennae successfully replicated diarrhea in mice models. Using 50 mg/ (kg/day) adenine for 14 days in combination with 10 g/(kg/day) Folium sennae decoction for 7 days caused kidney function injury in diarrhea mice. In addition, kidney function injury was accompanied by changing in intestinal functional enzyme activity and microbial activity.Cite this article as: Li X, Zhu J, Wu Y, Tan Z. Correlation between kidney function and intestinal biological characteristics of adenine and folium sennae-induced diarrhea model in mice. Turk J Gastroenterol. 2023; 34(1): 4-12.